PENGARUH BESARAN DANA INSENTIF DAERAH, TINGKAT KEMANDIRIAN DAERAH DAN RASIO BELANJA MODAL TERHADAP TINGKAT TRANSPARANSI PENGELOLAAN KEUANGAN PEMERINTAH DAERAH (Media Riset Akuntansi, 2022)
The existence mixed results and the phenomenon of the low transparency of local government financial management encourages researchers to re-examine the factors that affect the transparency of local government financial management. This study aims to determine the effect of the amount of regional incentive funds, the level of regional independence and the ratio of regional capital expenditures on the level of transparency of local government financial management on the local government website. The population of this research is all district and city governments in Indonesia who received the Regional Incentive Funds for the 2019 Fiscal Year in the amount of 311 local governments. The sampling technique used was purposive sampling. Based on this method, a sample size of 282 was obtained. The data analysis method used multiple linear regression analysis (multiple regression). The results showed that the amount of regional incentive funds had a positive effect on the level of transparency of local government financial management, while the level of independence and capital expenditure ratios had no effect on the level of transparency of local government financial management.